2013
DOI: 10.1099/ijs.0.048413-0
|View full text |Cite
|
Sign up to set email alerts
|

Pustulibacterium marinum gen. nov., sp. nov., a member of the family Flavobacteriaceae isolated from the Bashi Channel

Abstract: A Gram-reaction-negative, non-spore-forming, gliding, non-translucent, colourless or yellow, aerobic and elevated-colony-forming strain, designated E403T, was isolated from the Bashi Channel and subjected to a polyphasic taxonomic study. Strain E403T could grow in the presence of 0.3–8 % (w/v) NaCl, at 16–43 °C and at pH 6–9, and grew optimally at 28 °C, pH 8, in natural seawater medium. The respiratory quinones were MK-6 and MK-7. The major fatty acids were iso-C15 : 0, iso-C17 : 0 3-OH, iso-C15 : 1 G, summed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The description is as before (Wang G. et al, 2013) with the following modification. The genomic G+C content is c. 35–40%, the genome size is c. 4.0–4.5 Mbp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The description is as before (Wang G. et al, 2013) with the following modification. The genomic G+C content is c. 35–40%, the genome size is c. 4.0–4.5 Mbp.…”
Section: Discussionmentioning
confidence: 99%
“…The description is as before (Wang G. et al, 2013) with the following modification. The G+C content of the type-strain genome is 35.4%, its approximate size 4.21 Mbp, its GenBank deposit SAMN05216480.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, minor proportions of genes (53) assigned to COG functional categories (Table S4) are involved in the transport and metabolism of carbohydrates. This is different from the general preference for the metabolism of carbohydrates in members of the Flavobacteriaceae, which are often specialized in the degradation of recalcitrant polysaccharides and biomacromolecules [7]. In addition, a large number of genes were found to be involved in inorganic ion transport and metabolism (110) and signal transduction mechanisms (56) thereby indicating a high capacity of this strain to respond to environmental stimuli.…”
Section: Genome Featuresmentioning
confidence: 89%
“…At the time of writing, this family contains about 163 recognized genera according to the List of Prokaryotic Names with Standing in Nomenclature (LPSN) [6]. It has been reported that more than one-quarter of the members of this family are marine-related [7]. The members of the family Flavobacteriaceae play an important role in the uptake and degradation of dissolved and particulate organic matter and digest complex polysaccharides and other biomacromolecules [8].…”
mentioning
confidence: 99%